Diagnostic value of urodynamic bladder outlet obstruction to select patients for transurethral surgery of the prostate: Systematic review and meta-analysis. - Myong Kim; Chang Wook Jeong; Seung-June Oh (PLoS ONE)
Purpose To investigate the diagnostic value of urodynamic bladder outlet obstruction (BOO) in the selection of patients for transurethral surgery of the prostate. Materials and methods We systematically searched online PubMed, Embase, and Cochrane Library databases from January 1989 to June 2014. Results A total of 19 articles met the eligibility criteria for this systematic review. The eligible studies included a total of 2321 patients with a median number of 92 patients per study (range: 12-437). Of the 19 studies, 15 conducted conventional transurethral prostatectomy (TURP), and 7 used other or multiple modalities. In urodynamic bladder outlet obstruction (BOO) positive patients, the pooled mean difference (MD) was significant for better improvement of the International Prostate Symptom Score (IPSS) (pooled MD, 3.48; 95% confidence interval [CI], 1.72-5.24; p < 0.01; studies, 16; participants, 1726), quality of life score (QoL) (pooled MD, 0.56; 95% CI, 0.14-1.02; p = 0.010; studies, 9; participants, 1052), maximal flow rate (Qmax) (pooled MD, 3.86; 95% CI, 2.17-5.54; p < 0.01; studies, 17; participants, 1852), and post-void residual volume (PVR) (pooled MD, 32.46; 95% CI, 23.34-41.58; p < 0.01; studies, 10; participants, 1219) compared with that in non-BOO patients. Some comparisons showed between-study heterogeneity despite the strict selection criteria of the included studies. However, there was no clear evidence of publication bias in this meta-analysis. Conclusions Our meta-analysis results showed a significant association between urodynamic BOO and better improvements in all treatment outcome parameters. Preoperative UDS may add insight into postoperative outcomes after surgical treatment of benign prostatic hyperplasia.